A study on mechanical changes during the middle phase of the long jump approach run - Phukon, A. J.; Dhar, K. (ISBS Proceedings Archive: Vol. 43: Iss. 1, 2025)
This study investigated the mechanical adjustments made by elite long jumpers during the middle phase of the approach run. Kinematic data from the 5 senior Indian national level long jumpers (Personal Best:7.83±0.63m) with five high speed cameras (at resolution 1920s1080 with 120 frame per second). Further all the motion were quantified with Quintic (v.33). It was revealed that athletes maintained consistent step lengths while introducing subtle variations to manage velocity effectively. Study observed, some changes in torso touch-down angles; especially at 4LS were observed, indicating conscious efforts to optimize control without sacrificing step length. Contact duration (CD) varied across individuals, with athletes such as P1 and P4 increasing CD at 5LS and reducing it at 4LS, suggesting a dynamic modulation of ground contact to regulate approach velocity. The maximum knee angle during support influenced centre of mass lowering, potentially compromising velocity for take-off preparation. Despite individual differences, all athletes showed a gradual decrease in velocity, highlighting a controlled transition into the final steps. Overall, step length, knee angle, torso angle, and CD were closely linked to the athletes` aim of achieving optimal velocity before take-off.